Occurrence of basking shark Cetorhinus maximus in southern Portuguese waters: a two-decade survey - Couto, Ana (2019)
There is a general consensus that many shark species are declining in numbers. However, effective management measures often depend on knowing how trends in abundance and distribution are influenced by environmental conditions. Several efforts to describe the occurrence and distribution of basking sharks Cetorhinus maximus have been made in northern Europe, particularly around the UK, but nothing is known regarding their occurrence in southern areas, such as the south of Portugal. Using 2 decades of observational data collected in the south of Portugal, we show that the occurrence of basking sharks in the area was highly seasonal, with individuals being observed mainly during spring. Based on in situ and satellite-derived environmental variables and climate indices, we also demonstrate that temporal trends were associated with the beginning of the upwelling season and that the inter-annual changes were related to lower values of sea surface temperature, North Atlantic Oscillation index, upwelling index, 2-mo lagged chlorophyll a and 3-mo lagged Atlantic Multidecadal Oscillation index, and higher values of 2-mo lagged upwelling index. These findings suggest that basking sharks are associated with the expansion of cold waters following upwelling events in the region, probably due to the aggregation and increase of zooplankton. Although the temperature recorded during our study years ranged from 14 to 24 degrees C, sharks were mainly observed when temperatures were lower than 20 degrees C, corroborating their preference for colder water. This study provides the first knowledge on the habitat use of basking sharks in southern European Atlantic areas.